Genome-Scale CRISPR Knockout Screening Identifies BACH1 as a Key Regulator of Aflatoxin B1-Induced Oxidative Damage - Jinfu Zhang; Siyi Hu; Changzhi Zhao; Yuan Zhou; Lu Zhang; Hailong Liu; Peng Zhou; Sheng Li; Liangliang Fu; Zhuqing Zheng; Yue Xiang; Xuewen Xu; et al. (Antioxidants, 2022)
Aflatoxin B1 (AFB1) is amongst the mycotoxins commonly affecting human and animal health, raising global food safety and control concerns. The mechanisms underlying AFB1 toxicity are poorly understood. Moreover, antidotes against AFB1 are lacking. Genome-wide CRISPR/Cas9 knockout screening in porcine kidney cells identified the transcription factor BTB and CNC homolog 1 (BACH1) as a gene required for AFB1 toxicity. The inhibition of BACH1 expression in porcine kidney cells and human hepatoma cells resulted in increased resistance to AFB1. BACH1 depletion attenuates AFB1-induced oxidative damage via the upregulation of antioxidant genes. Subsequently, virtual structural screening identified the small molecule 1-Piperazineethanol, α-[(1,3-benzodioxol-5-yloxy)methyl] -4-(2-methoxyphenyl) (M2) as an inhibitor of BACH1. M2 and its analogues inhibited AFB1-induced porcine and human cell death in vitro, while M2 administration significantly improved AFB1-induced symptoms of weight loss and liver injury in vivo. These findings demonstrate that BACH1 plays a central role in AFB1-induced oxidative damage by regulating antioxidant gene expression. We also present a potent candidate small-molecule inhibitor in developing novel treatments for AFB1 toxicity.